2023
DOI: 10.1155/2023/8437073
|View full text |Cite
|
Sign up to set email alerts
|

Population Density of Wild Animals and Their Conflict in Konasa_Pulasa Community Conserved Forest, Omo Valley, Southern Ethiopia

Mesfin Matusal,
Aberham Megaze,
Taye Dobamo

Abstract: Human-wildlife conflict presents an increasing challenge to conservation, particularly in densely populated parts of low-income countries. An investigation on wild animal population density and its conflict was carried out from December 2019 to May 2020 in the Konasa_Pulasa Community Conserved Forest, Omo Valley, Southern Ethiopia: implications for wildlife conservation. The distance sampling method was used to estimate the population status of wild animals in an area of 187.57 km2. Human-wild animal conflict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
(128 reference statements)
0
1
0
Order By: Relevance
“…Respondents who were in favour of wildlife cited several reasons, including the fact that it preserves the environment, draws tourists, offers sustenance during times of extreme food scarcity, is visually beautiful, and will be vital for future generations. According to Matusal et al [ 33 ], respondents who had negative attitudes towards wildlife species observed wild animals as possible crop raiders, livestock depredators, disease carriers, and threats to humans. Conversely, respondents who had neutral attitudes did not offer any explanation for their lack of concern for wildlife.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents who were in favour of wildlife cited several reasons, including the fact that it preserves the environment, draws tourists, offers sustenance during times of extreme food scarcity, is visually beautiful, and will be vital for future generations. According to Matusal et al [ 33 ], respondents who had negative attitudes towards wildlife species observed wild animals as possible crop raiders, livestock depredators, disease carriers, and threats to humans. Conversely, respondents who had neutral attitudes did not offer any explanation for their lack of concern for wildlife.…”
Section: Discussionmentioning
confidence: 99%